Desenvolvimento e avaliação imunogênica de duas vacinas baseadas no GnRH suíno com potencial uso em imunocastração - Andreetta, Angélica Teresinha (2017)
Gonadotrophin releasing hormone (GnRH) has as its main function regulate the reproduction of vertebrates. Active immunization against GnRH has been used strategically to neutralize endogenous GnRH and to promote immunocastration of vaccinated animals. This method replaces surgically castrated and increases the quality of life of the animals. In this work, we present the development and evaluation of two experimental vaccines based on swine GnRH with the potential to neutralize endogenous GnRH in rats. The genes encoding the recombinant proteins Construct007 (carrier 001 + GnRH) and constructCTBsGnRh7-24His (carrier 002 + GnRH) were synthesized by Amplicon Vaccine (Pullman, USA) and cloned into the expression vector pET24. Thereafter, the constructs were chemically transformed into Escherichia coli strain ER2566 and the expression of the recombinant proteins was induced overnight with IPTG. After cell lysis, the proteins were purified by liquid protein chromatography using a column loaded with nickel ions. After dialysis of the proteins in PBS (pH 7.2), the experimental vaccines were formulated with 50 μg of the pure antigens potentiated with 15% Montanide Gel 01 adjuvant (Seppic, France). A total of 12 male adult Wistar rats were randomly separated into 3 groups. The first two groups were immunized intramuscularly with either the Construct007 or constructCTBsGnRh7-24His vaccine. The third group was inoculated with PBS + Montanide Gel 01. The vaccination protocol consisted of 2 doses with a 21 day interval. Clinically, the safety of formulations and testicular development (testis size and weight), and immunologically the ability of vaccines to induce anti-GnRH pig antibodies were evaluated. Animals immunized with Construct007-based vaccine showed significantly higher antibody titers compared to those vaccinated with recombinant constructCTBsGnRh7-24His protein. Clinically, the antibody response induced by the Construct007 vaccine was able to neutralize the endogenous GnRH of rats, significantly reducing the testicular development of these animals compared to control animals (PBS + Montanide Gel 01), as well, compared to those vaccinated with the constructCTBsGnRh7-24His protein. Taking into account the safety and functional blocking ability of GnRH induced by the Construct007 formulation, it becomes evident the potential use of this experimental vaccine in a future study in the immunization target species. This dissertation contains data that are potentially patentable and should be kept confidential until 13 xv they are processed by patent and international regulatory agencies. Key words: GnRH, Vaccines, Swine, immunocastration.